Involvement of End Users in the Development of Serious Games for Health Care Professions Education: Systematic Descriptive Review - Marc-André; Véronique Dubé; Sylvie Cossette; Alexandra Lapierre; Guillaume Fontaine; Marie-France Deschênes; Patrick Lavoie (JMIR Publications, 2021)
BackgroundOn the basis of ethical and methodological arguments, numerous calls have been made to increase the involvement of end users in the development of serious games (SGs). Involving end users in the development process is considered a way to give them power and control over educational software that is designed for them. It can also help identify areas for improvement in the design of SGs and improve their efficacy in targeted learning outcomes. However, no recognized guidelines or frameworks exist to guide end users' involvement in SG development. ObjectiveThe aim of this study is to describe how end users are involved in the development of SGs for health care professions education. MethodsWe examined the literature presenting the development of 45 SGs that had reached the stage of efficacy evaluation in randomized trials. One author performed data extraction using an ad hoc form based on a design and development framework for SGs. Data were then coded and synthesized on the basis of similarities. The coding scheme was refined iteratively with the involvement of a second author. Results are presented using frequencies and percentages. ResultsEnd users' involvement was mentioned in the development of 21 of 45 SGs. The number of end users involved ranged from 12 to 36. End users were often involved in answering specific concerns that arose during the SG design (n=6) or in testing a prototype (n=12). In many cases, researchers solicited input from end users regarding the goals to reach (n=10) or the functional esthetics of the SGs (n=7). Most researchers used self-reported questionnaires (n=7). ConclusionsResearchers mentioned end users' involvement in the development of less than half of the identified SGs, and this involvement was also poorly described. These findings represent significant limitations to evaluating the impact of the involvement of end users on the efficacy of SGs and in making recommendations regarding their involvement.